Analisis Yuridis Penghentian Penuntutan Berdasarkan Restorative Justice (Studi Kasus Penghentian Penuntutan Di Kejaksaan Negeri Timor Tengah Utara) - Maubila, James; Fallo, Debby F. Ng.; Amalo, Heryanto (Law Faculty, Nusa Cendana University, 2023)
Restorative justice is a law enforcement system centered on perpetrators, victims, and communities. Restorative justice is a new movement in the field of victimology and criminology, therefore restorative justice allows perpetrators, victims, and affected communities to be directly involved in processing such crimes. Research entitled Juridical analysis of termination of prosecution based on Restorative Justice (case study of termination of prosecution in the North Central Timor State Attorney's Office) aims to determine and juridically analyze the termination of prosecution based on restorative justice. The formulation of the problem in this study is (1) How is the existence of termination of prosecution based on restorative justuce in the justice system in Indonesia? (2) What is the chronology and process of applying the termination of prosecution based on restorative justice in the North Central Timor District Attorney's Office? In this study, the author used empirical juridical legal research methods. Empirical juridical legal research is legal research that examines applicable legal provisions and what happens in reality in society with the intention of knowing and finding the facts and data needed, after the required data is collected then leads to the identification of problems that ultimately lead to solving problems. The results showed (1) The existence and mechanism for stopping prosecution based on restorative justice based on the Prosecutor's Regulation of the Republic of Indonesia Number 15 of 2020. (2) Chronology and process of implementing restorative justice in the North Central Timor State Attorney's Office. If the termination of prosecution according to Restorative justice will be carried out, there must be a peace agreement between the Victim and the Perpetrator and has fulfilled the requirements as stated in the Prosecutor's Regulation No. 15 of 2020 concerning the termination of Prosecution Based on Restorative Justice.